2022
DOI: 10.1186/s13023-022-02452-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of X-linked hypophosphatemia in Spain

Abstract: Background Health-related quality of life (HRQoL) of patients with X-linked hypophosphatemia (XLH) is lower than that of both the general population and the patients with other chronic diseases, mainly due to diagnostic delay, treatment difficulties, poor psychosocial support, and problems with social integration. Early diagnosis and optimal treatment are paramount to control the disease in patients with XLH, avoid complications, and maintain or improve their HRQoL. We, therefore, analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Both XLH study populations reported a lower mean SF-36-PCS than mean SF-36-MCS suggesting that the physical impact of the condition may be greater than the mental impact. We found mean HRQL of adults with XLH (EQ-5D-5L = 0.651) to be higher than that of a Spanish study of adults with XLH (EQ-5D-5L = 0.562) [ 49 ]. This difference may be due to limited generalisability between UK and Spanish populations or the latter study identifying their participants through specialized clinics which may infer a more severe case mix.…”
Section: Discussionmentioning
confidence: 96%
“…Both XLH study populations reported a lower mean SF-36-PCS than mean SF-36-MCS suggesting that the physical impact of the condition may be greater than the mental impact. We found mean HRQL of adults with XLH (EQ-5D-5L = 0.651) to be higher than that of a Spanish study of adults with XLH (EQ-5D-5L = 0.562) [ 49 ]. This difference may be due to limited generalisability between UK and Spanish populations or the latter study identifying their participants through specialized clinics which may infer a more severe case mix.…”
Section: Discussionmentioning
confidence: 96%
“…Notwithstanding, the health‐related quality of life (HRQoL) of XLH patients remains poor even with conventional treatment, indicating the need for better treatment options. ( 88 )…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the health-related quality of life (HRQoL) of XLH patients remains poor even with conventional treatment, indicating the need for better treatment options. (88) Burosumab Burosumab is a fully human monoclonal antibody against FGF23. In 2018, the European Medicines Agency (EMA) approved its use in EU for XLH in children from the age of 1 year and adolescents with a growing skeleton.…”
Section: Conventional Therapymentioning
confidence: 99%
“…The early onset osteoarthritis is also thought to be a consequence of bone and joint deformation during growth [1,9,10]. All people with XLH, irrespective of age, describe their condition as having a severe negative impact on their physical function, mobility and health-related quality of life [7,[11][12][13][14]. 'Conventional therapy' for the treatment of XLH includes oral phosphate, given daily in multiple doses, and active vitamin D metabolites or analogues.…”
Section: Introductionmentioning
confidence: 99%